Selenium and copper status: potential signposts for neurological remission after traumatic spinal cord injury - Seelig, Julian; Heller, Raban; Haubruck, Patrick (Journal of trace elements in medicine and biology, 2020)
Introduction - Traumatic Spinal Cord Injury (TSCI) is a severe incident resulting in loss of motor and sensory function caused by complex pathological mechanisms including massive oxidative stress and extensive inflammatory processes. The essential trace elements selenium (Se) and copper (Cu) play crucial roles as part of the antioxidant defense. - Hypothesis - Remission after TSCI is associated with characteristic dynamics of early changes in serum Cu and Se status. - Study design - Single-center prospective observational study. - Patients and methods - Serum samples from TSCI patients were analyzed (n=52); 21 recovered and showed a positive abbreviated injury score (AIS) conversion within 3 months (G1), whereas 21 had no remission (G0). Ten subjects with vertebral fractures without neurological impairment served as control (C). Different time points (at admission, and after 4, 9, 12, and 24h) were analyzed for total serum Se and Cu concentrations by total reflection X-ray fluorescence, and for Selenoprotein P (SELENOP) and Ceruloplasmin (CP) by sandwich ELISA. - Results - At admission, CP and SELENOP concentrations were higher in the remission group (G1) than in the non-remission group (G0). Within 24h, there were marginal changes in Se, SELENOP, Cu and CP concentrations in the groups of controls (C) and G0. In contrast, these parameters decreased significantly in G1. Binary logistic regression analysis including Cu and Se levels at admission in combination with Se and CP levels after 24h allowed a prediction for potential remission, with an area under the curve (AUC) of 87.7% (CI: 75.1%-100.0%). - Conclusion - These data indicate a strong association between temporal changes of the Se and Cu status and the clinical outcome after TSCI. The dynamics observed may reflect an ongoing redistribution of the trace elements in favor of a better anti-inflammatory response and a more successful neurological regeneration.